The Book of Tea - Okakura, Kakuzo, 1862-1913 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Book of Tea" by Kakuzo Okakura is an essay written in 1906 that links the Japanese tea ceremony to the aesthetic and cultural values of Japanese life. Originally written in English for Western readers, it explores how Teaism teaches simplicity, harmony, and humility. Okakura protests Western misunderstandings of Eastern culture and argues that the principles of tea offer a universal remedy for conflict. The book discusses Zen, Taoism, and the philosophy of finding beauty in imperfection. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Book_of_Tea
Release date is 1997-01-01
Produced by Matthew, Gabrielle Harbowy, and David Widger
Keywords: Tea; Japan -- Social life and customs; Japanese tea ceremony